'Not everyone's gonna like me': Accounting for race and racism in sex and dating web services for gay and bisexual men. (February 2016) - Callander, Denton; Holt, Martin; Newman, Christy E.
Sexual racism can be thought of as a specific form of racial prejudice enacted in the context of sex and dating. It is a contentious issue among gay and bisexual men looking for partners online. This study draws upon 14 in-depth interviews conducted between August and October 2012 with gay and bisexual men of colour in Australia. Data were thematically analysed to identify interpretations and experiences of, and reactions to sexual racism online. Understandings of online sexual racism were diverse, ranging from clear ideas about racist and non-racist practices to more ambiguous and contextual interpretations. Nevertheless, all participants described experiences of sexual racism while seeking partners online, which were, in some cases, largely indistinguishable from generic forms of racism. Most described experiences of subtle racism, but there were also cases of blatant and aggressive racial prejudice. Finally, men reacted in a range of ways when confronted with online sexual racism, with strategies ranging from disconnection to adaptation through to confrontation. Our findings highlight that sexual racism – as an expression of racism generally – is an ongoing issue for men who seek out other men online, and that men engage in a range of strategies for mitigating the negative effects of racial prejudice in this domain.